2014
DOI: 10.1118/1.4863482
|View full text |Cite
|
Sign up to set email alerts
|

ITAR: A modified TAR method to determine depth dose distribution for an ophthalmic device that performs kilovoltage x‐ray pencil‐beam stereotaxy

Abstract: Equipment selection, measurement techniques, and formalism for the determination of dose rate to the macula during stereotaxy for AMD have been determined and are strongly recommended by the authors of this paper to be used by clinical medical physicists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The first one has been used for measurements of the Xoft x-ray source, 6 the INTRABEAM unit, 8 and the Esteya system, 10 as well as for measurements with a 100 kVp source and field sizes as small as 4.2 mm diameter. 18 Measurements with both chambers were not compared in those previous studies. Recently, Fulkerson et al 7 used both the T34013 and the A20 chambers for measurements of the Xoft x-ray source and concluded that the first chamber had a large and counterintuitive magnitude in the stem effect, making it unsuitable for the dose measurements, so the use of the A20 chamber was since then recommended for reference dosimetry of the Xoft x-ray tube.…”
Section: Introductionmentioning
confidence: 99%
“…The first one has been used for measurements of the Xoft x-ray source, 6 the INTRABEAM unit, 8 and the Esteya system, 10 as well as for measurements with a 100 kVp source and field sizes as small as 4.2 mm diameter. 18 Measurements with both chambers were not compared in those previous studies. Recently, Fulkerson et al 7 used both the T34013 and the A20 chambers for measurements of the Xoft x-ray source and concluded that the first chamber had a large and counterintuitive magnitude in the stem effect, making it unsuitable for the dose measurements, so the use of the A20 chamber was since then recommended for reference dosimetry of the Xoft x-ray tube.…”
Section: Introductionmentioning
confidence: 99%